10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
For cervical cancer, the choice between definitive radiotherapy (RT) and surgery has long been a topic of debate. Clinical factors, including histology and tumor burden, have been examined in prior studies. Given recent advances in RT and the incorporation of concurrent chemotherapy, our study seeks to assess the optimal treatment modality for cervical cancer in current clinical practice. The cancer registry database of a medical center was screened for cervical cancer patients. Patients receiving curative intent RT or surgery were included. Clinicopathological factors and treatment outcomes were retrospectively collected. The disease-free survival (DFS) and overall survival (OS) were analyzed using Cox regression and Kaplan-Meier analyses. From 2007 to 2021, 369 squamous cell carcinoma (SCC) and 108 adenocarcinoma (AC) cases were enrolled. AC had an increasing proportion over time and was associated with worse survival. Comparing RT to surgery, RT was associated with inferior survival in both early-stage AC (DFS, HR: 8.29, p < 0.001, 95% CI: 3.21-21.42) and SCC group (DFS, HR: 4.01, p < 0.001, 95% CI: 1.99-8.08). The difference was more robust in those with tumors smaller than 4 cm. For advanced-stage disease, the inferiority of RT was observed in the SCC (DFS, HR: 1.85, p = 0.020, 95% CI: 1.10-3.11), but not AC group. There was no statistically significant intergroup difference observed between the AC and SCC groups regarding DFS of RT versus surgery. In our analysis, AC was an independent poor prognostic factor. Despite the addition of concurrent chemotherapy and advanced RT techniques, surgery-based treatment was still associated with superior survival for early-stage cervical cancer.